The effects of strenuous exercise and nutrition on the immune functions of elite athletes - Jabbar Ashour, T. J.; Ali, C.; Youssef, H. M. (European Journal of Physical Education and Sport Science, 2017)
The intense activities carried out by athletes result in them undergoing acute and chronic stress and this in turn will suppress their immune system as well as increase their oxidative species generation. On top of that, these athletes has a tendency to consume less calories than what is needed and they also have a tendency to avoid consuming fats, and the latter action may affect their immune system and anti-oxidant mechanisms. The stress caused by the exercise is dependent upon how intense the exercise is and its duration, and it is relative to the athlete`s maximum capacity. The depletion of glycogen in the muscles affects the performance of the exercise as well as increases the stress. However, the glycogen stores can be protected if there is an increase in fat oxidation (glycogen sparing). Athletes should have balanced diets whereby the total calories consumed is the same as that expended and the carbohydrates and fats that are utilized must be replenished. However, many athletes fail to meet these important basic criteria thus compromising their glycogen or fat stores, and do not consume sufficient essential fats and micronutrients which are required to maintain their intense exercise, immune competence and anti-oxidant defense. Over-training or malnourishment may result in an increased risk of infections. In some cases, the intake of micronutrient supplements may strengthen the immune system and make up for the deficiency of the essential nutrients. Any nutrient deficiencies in the athletes` diet must be compensated with nutritional supplements, but it must not be over compensated. If the above-mentioned rules are complied with and the training are properly regulated so that there is no overtraining, the immune system can be maintained at the optimal level and this in turn will reduce the risk of diseases.